2001
DOI: 10.1046/j.1365-2362.2001.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exocrine pancreatic function in cystic fibrosis: one mild CFTR mutation does not exclude pancreatic insufficiency

Abstract: Patients who carry two 'severe' mutations develop pancreatic insufficiency, whereas those who carry at least one 'mild' usually remain pancreatic sufficient. However, the presence of one mild mutation does not exclude pancreatic insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 22 publications
6
30
0
Order By: Relevance
“…Fecal concentrations of E1 were < 30 μg/g of stool in all PI CF patients (9 μg [6][7][8][9][10][11] At the baseline, no differences between the groups with regard to the diameter of the pancreatic duct in the head, body, and tail of the pancreas were stated. The pancreas in PI CF patients was narrower than in PS CF patients when measured at the level of the head, the body, and the tail.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Fecal concentrations of E1 were < 30 μg/g of stool in all PI CF patients (9 μg [6][7][8][9][10][11] At the baseline, no differences between the groups with regard to the diameter of the pancreatic duct in the head, body, and tail of the pancreas were stated. The pancreas in PI CF patients was narrower than in PS CF patients when measured at the level of the head, the body, and the tail.…”
Section: Resultsmentioning
confidence: 90%
“…It was shown that between 10% and 28% of CF patients are PS [6][7][8][9] and this phenotypic property is not readily predicted by the genotype [10]. Only PS CF patients may be affected by pancreatitis, which may lead to insufficiency in the long term [8].…”
Section: Introductionmentioning
confidence: 99%
“…26 Other mutations in the CFTR gene such as G542X, G551D, and N1303K occur in greater than 1% in the CF population and are associated with severe pancreatic insufficiency. 23,27 Recently, carriers of the I148T mutation have received more attention because I148T has been found in association with the 3199del6 mutation, which may be necessary for the classic CF phenotype. 28 Because of the complexity of both the mutations and the phenotypes, a high-throughput mutation scanning method to screen the entire coding region of the CFTR gene may provide valuable clinical information regarding CF genotypes and respective phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The Polish population differs slightly from the European average. For example, F508del in CF chromosomes is less frequent (~55% vs 70%) while the 3849 + 10kbC > T mutation is significantly more frequent (~4% vs 0.2%) (Witt et al 1990;CFGA Consortium 1994;Walkowiak et al 2001). The frequency of the East/Central-European-specific 2,3del21kb mutation in Polish patients (~3%, based on our recent unpublished data), although within the range observed in a number of Central and East European countries (16%), is much higher than in Western/Southern Europeans (only sporadic cases observed) (Dork et al 2000).…”
Section: Introductionmentioning
confidence: 99%